2018
DOI: 10.1088/1742-5468/aaa8f7
|View full text |Cite
|
Sign up to set email alerts
|

Revisit the faster-is-slower effect for an exit at a corner

Abstract: The faster-is-slower effect (FIS), which means that crowd at a high enough velocity could significantly increase the evacuation time to escape through an exit, is an interesting phenomenon in pedestrian dynamics. Such phenomenon had been studied widely and has been experimentally verified in different systems of discrete particles flowing through a centre exit. To experimentally validate this phenomenon by using people under high pressure is difficult due to ethical issues. A mouse, similar to a human, is a ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…In another study, Lin et al [23] explored the effect of different levels of stimuli on the evacuation of mice through centrally located bottlenecks. However, Chen et al [21] reproduced the experiments conducted by Lin et al [23] with the same breed of mice, and exit width but, additionally, changed the position of the egress point from the centre to the corner of the wall. Chen et al [21] observed that the evacuation from corner exits was not affected significantly by the level of stimulus (mean evacuation time for each mouse was approximately 3.5 s in all conditions [21]) but in the case of the centrally located exit, the evacuation time varied from 2.5 s to 5.1 s as the stimulus was increased from low level to high level [21].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In another study, Lin et al [23] explored the effect of different levels of stimuli on the evacuation of mice through centrally located bottlenecks. However, Chen et al [21] reproduced the experiments conducted by Lin et al [23] with the same breed of mice, and exit width but, additionally, changed the position of the egress point from the centre to the corner of the wall. Chen et al [21] observed that the evacuation from corner exits was not affected significantly by the level of stimulus (mean evacuation time for each mouse was approximately 3.5 s in all conditions [21]) but in the case of the centrally located exit, the evacuation time varied from 2.5 s to 5.1 s as the stimulus was increased from low level to high level [21].…”
Section: Introductionmentioning
confidence: 86%
“…Other studies, however, have investigated the impact of the location of exit points on the flow, i.e. directly comparing the flows for corner exit points and centrally located exit points [16,21]. For example, Shiwakoti and Sarvi [22] investigated the movement of ants from an enclosed area via a corner and centrally located exit points and then scaled and simulated the evacuation of humans from a room with the exit points similarly located.…”
Section: Introductionmentioning
confidence: 99%
“…found that enough exit width enabling two mice pass the exit side by side could avoid 'faster-is-slower' effect [135]. Further, Chen et al (2018) found that 'faster-is-slower' effect was less likely to occur at corner exits than middle exits [136]. In another mice egress experiments, Oh and Park (2017) examined the influence of the exit angle on egress dynamics with a group of 50 mice [137].…”
Section: Egress and Ingressmentioning
confidence: 99%
“…Journal of Advanced Transportation with human crowds [128] Journal of Advanced Transportation were further utilized to test a method that can measure the steady flow state [188] Journal of Advanced Transportation the burning of joss-sticks should be presented (i) The effect of obstacle was further analyzed [134] (ii) The effect of exit position was further analyzed [136] (iii) The effect of bottleneck width was further analyzed [135]…”
mentioning
confidence: 99%
“…Video monitoring of daily routines in a farm was collected by measuring the time lapses between the passages of consecutive sheep, some features of the flow regime can be assessed and the effect of increasing the door size and the performance of an obstacle placed in front of it were evaluated. Lin et al [17,18] and Chen et al [19] conducted a series of experiments by driving the mice to pass through an exit, with or without an obstacle before it. The study shows that the presence of an obstacle in front of an exit can improve or deteriorate the evacuation efficiency depending on the nearby geometry.…”
Section: Introductionmentioning
confidence: 99%